Management measures for ancient settlements threatened by coastal hazards at Boca do Rio, Algarve, Portugal - Carrasco, Ana Rita (2015)
Coastal areas are dynamic by nature, with physical changes occurring over various time scales. When these changes manifest themselves as a landward movement of the shoreline occurring on human time scales, the quantification of erosion rates becomes important (Moore and Griggs, 2002). The evolution of coastal retreat results from several relationships between external and local processes, with many variables potentially affecting the rate and manner of retreat. Currently, the Portuguese coastal zone is strongly affected by coastal erosion in association with an important sedimentary deficiency, which was initiated around the beginning of the 20th century, and became strongly enhanced after the 1930s-1940s (Dias and Neal, 1992). At present, shoreline retreat rates reach the order of a few meters per year in some parts of the Portuguese coastline (Dias and Neal, 1992). A decrease in fluvial sediment transport and a continuing rise in sea level are two of the main causes of coastal erosion not only in Portugal, but also in other parts of the world. Over shorter timescales, storms are also able to cause coastal retreat. Such retreat is only reversible on a human scale (years to decades) if sediment starvation is naturally or artificially stopped (e.g., by beach nourishment or dune building) (Carter, 1988). Changes in storm patterns and incident wave climates may result in beach realignments and higher rates of foreshore change.